2010
DOI: 10.1002/eji.200939419
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin induces early human B‐cell proliferation and differentiation

Abstract: Thymic stromal lymphopoietin (TSLP) is a cytokine that binds the IL-7-receptor-a chain and a unique TSLP receptor (TSLPR) chain. The role of TSLP in human B-cell development has not been elucidated. We show that TSLPR transcripts are expressed most prominently in CD341 cells from fetal liver and BM. In general, cell surface expression of TSLPR was low, except on a subset of multilineage-commited progenitor cells. TSLP induced the tyrosine-phosphorylation of STAT5 and the proliferation of multilineage-commited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 48 publications
2
42
0
3
Order By: Relevance
“…hTSLP has been shown to increase the in vitro production of normal human B-cell precursors 9 despite their low levels of CRLF2 expression (Online Supplementary Figure S2). Thus, expansion of normal human B-cell precursors provides a sensitive in vivo functional test of the hTSLP produced in our xenograft model.…”
Section: Htslp Produced In Xenograft Mice Exerts In Vivo Functional Ementioning
confidence: 99%
“…hTSLP has been shown to increase the in vitro production of normal human B-cell precursors 9 despite their low levels of CRLF2 expression (Online Supplementary Figure S2). Thus, expansion of normal human B-cell precursors provides a sensitive in vivo functional test of the hTSLP produced in our xenograft model.…”
Section: Htslp Produced In Xenograft Mice Exerts In Vivo Functional Ementioning
confidence: 99%
“…Studies have also shown that TSLP enhances proliferation of CD4ϩ and CD8ϩ T cells activated by T-cell receptor stimulation (8,9). In mice, TSLP can also activate dendritic cells (10), CD4ϩ T cells (11), and CD8ϩ T cells (12), and is important for pre-B-cell development (13).…”
Section: Thymic Stromal Lymphopoietin (Tslp)mentioning
confidence: 99%
“…70 CRLF2 forms a heterodimeric receptor with interleukin-7 receptor alpha for the cytokine thymic stromal lymphopoietin. [78][79][80] thymic stromal lymphopoietin/CRLF2 signaling has a role in dendritic cell development, 81 T cell responses, 82,83 allergic inflammation, [84][85][86] and promotes the proliferation of normal and leukemic B cells, [87][88][89][90][91] but at present the requirement for CRLF2 signaling in normal B-lymphoid ontogeny is unclear, and it may be dispensable. 88,92 The downstream mediators of thymic stromal lymphopoietin/CRLF2 signaling are poorly defined and may differ between human and mouse, and activation of JAK-STAT signaling has been described for the human but not CRLF2.…”
Section: Genetic Characterization Of Bcr-abl1-like Phà Allmentioning
confidence: 99%